Patient-reported outcomes provide evidence for increased depressive symptoms and increased mental impairment in giant cell arteritis - Froehlich, Matthias; Zahner, Antonia; Schmalzing, Marc; Gernert, Michael; Strunz, Patrick-Pascal; Hueper, Sebastian; Portegys, Jan; Schwaneck, Eva Christina; Gadeholt, Ottar; Kübler, Andrea; Hewig, Johannes; Ziebell, Philipp (Frontiers in Medicine, 2023)
Objectives: The spectrum of giant cell arteritis (GCA) and polymyalgia rheumatica (PMR) represents highly inflammatory rheumatic diseases. Patients mostly report severe physical impairment. Possible consequences for mental health have been scarcely studied. The aim of this study was to investigate psychological well-being in the context of GCA and PMR. Methods: Cross-sectional study with N = 100 patients with GCA and/or PMR (GCA-PMR). Patient-reported outcomes (PROs) were measured using the Short Form 36 Version 2 (SF-36v2) and visual analogue scale (VAS) assessment. Moreover, the Patient Health Questionnaire 9 (PHQ-9) was used in 35 of 100 patients to detect depression. To compare PROs with physician assessment, VAS was also rated from physician perspective. To assess a possible association with inflammation itself, serological parameters of inflammation (C-reactive protein [CRP], erythrocyte sedimentation rate [ESR]) were included. Results: In all scales of the SF-36v2 except General Health (GH) and in the physical and mental sum score (PCS, MCS), a significant impairment compared to the German reference collective was evident (MCS: d = 0.533, p < 0.001). In the PHQ-9 categorization, 14 of the 35 (40%) showed evidence of major depression disorder. VAS Patient correlated significantly with PHQ-9 and SF-36 in all categories, while VAS Physician showed only correlations to physical categories and not in the mental dimensions. Regarding inflammatory parameters, linear regression showed CRP to be a complementary significant positive predictor of mental health subscale score, independent of pain. Conclusion: PRO show a relevant impairment of mental health up to symptoms of major depression disorder. The degree of depressive symptoms is also distinctly associated with the serological inflammatory marker CRP.